STRATEGI PENGEMBANGAN HUTAN RAKYAT DI KABUPATEN BARRU - Nadrah Nadrah; Nuraeni Nuraeni; Suriyanti Suriyanti (Percetakan Umi Toaha Makassar, 2022)
Thisresearch was conducted with the objectives of: (1) Identifying community forest management in Barru Regency, (2) Identifying community forest farmers' acceptance in Barru Regency, (3) Identifying external and internal factors in community forest development in Barru Regency, (4) Formulating development strategy in the development of community forests in Barru Regency. The research was carried out from December 2020 to January 2021. Locations in Soppeng Riaja District, Barru Regency, namely the Forest Farmers Group (KTH) Sipakatau Siddo Village and KTH Megabuana Paccekke Village. The results showed that the management of community forests in Barru Regency has an agroforestry pattern with a planting pattern of wood, food, plantation, and other crops. The average income of community forest farmers is Rp. 10,874,600/person or an average of Rp.11,187,860/hectare. Internal factors that become strengths and weaknesses in the development of community forests in Barru Regency are identified through indicators of land area, labor, experience in managing community forests and acceptance of community forest farmers. External factors that become opportunities and threats are identified through access to information in marketing the results of businesses in community forest, government attention to community forest management, government assistance to community forest farmers, the role of Forest Farmers Groups (KTH) in helping farmers market products from community forests. , the selling price of community forest products and training of farmers on community forests. Based on the results of the SWOT analysis, it was found that the strength score was greater than the weakness with a difference of 2.60 and the opportunity score was greater than the threat with a difference of 2.83. This shows that the strategy formulation used is Strengths (S) – Opportunities (O) by using strengths to take advantage of opportunities.